Selective C3–H nitration of 2-sulfanilamidopyridines with tert-butyl nitrite. Issue 16 (8th July 2022) - Wang, Huifang; Ge, Guoping; Gao, Wenqing; Luo, Junfei; Tang, Keqi
Abstract : A selective C3–H nitration of bioactive 2-sulfanilamidopyridine derivatives, including corticosteroid 11- β -dehydrogenase isozyme, secretory phospholipase A2 inhibitor and human neutrophil elastase inhibitor, has been reported. Abstract : We report a selective C3–H nitration of 2-aminopyridines using the N -sulfonyl group as a directing group. This method provides access to a variety of C3 nitrated 2-sulfanilamidopyridine derivatives. The N -sulfonyl protecting group could also act as a good directing group for ortho -nitration of 3- and 4-aminopyridines. In addition, the late-stage selective nitration of corticosteroid 11-β-dehydrogenase isozyme, secretory phospholipase A2 inhibitor and human neutrophil elastase inhibitor was successfully achieved under the standard conditions.